Long-term Therapeutic Success of Intravenous Rituximab in 26 Patients with Indolent Primary Cutaneous B-cell Lymphoma - Stefanie Porkert; Pamela Mai; Constanze Jonak; Felix Weihsengruber; Klemens Rappersberger; Wolfgang Bauer; Ingrid Simonitsch-Klupp; Markus Raderer; Julia Valencak (Medical Journals Sweden, 2021)
Systemic monotherapy with rituximab is a well-known treatment approach for primary cutaneous follicle centre lymphoma and primary cutaneous marginal zone lymphoma. Both have excellent prognosis despite high relapse rates. To investigate the long-term effectiveness and clinical outcome of intravenous rituximab at a dose of 375 mg/m2 once weekly, data for 26 patients (17 primary cutaneous follicle centre lymphoma and 9 primary cutaneous marginal zone lymphoma) were analysed retrospectively. Complete remissions occurred in 20 (77%) and partial remissions in 6 patients (23%), demonstrating an overall response rate of 100%. The relapse rate was 52.9% in primary cutaneous follicle centre lymphoma and 88.9% in primary cutaneous marginal zone lymphoma. Ongoing complete remissions after therapy with rituximab were observed in 9 patients (34.6%) with a median progression-free survival of 161 months (13.4 years). These results confirm that intravenous rituximab is an effective and well-tolerated treatment with durable responses in a relevant percentage of patients at a median follow-up of 148 months (12.3 years).